Caracterização morfo-agronômica e avaliação da resistência em acessos de fava ao mosaico dourado e à antracnose - Silva Neto, João Ribeiro da (2010)
The aim of this study was to characterize morphological and agronomic, degree of resistance to golden mosaic and anthracnose on bean accessions, was evaluated seventy accessions of Phaseolus lunatus L., from the active germplasm banks of the Federal University of Piauí and the Federal Rural de Pernambuco, and seeds from the states of Alagoas, Pernambuco, Sergipe and Paraíba, all taken directly from fields and / or fairs, planted in crop year 2008. Seeds were sown in early May the waters. The characterization was made with plant characteristics, flower, pod and seed, according to recommendations of IPGRI. To evaluate the impact of the golden mosaic design was randomized blocks with two replicates in characterization and evaluation of resistance to anthracnose utilized is a single block, represented by seventy access, single row, the severity of the fungus was evaluated in leaves of plants, a greater severity during the rainy season, since the action of whitefly and virus incidence occurred in the dry season, causing damage to production of lima bean. The accessions showed different degrees of polymorphism in relation to all traits; incidence of bean golden mosaic and anthracnose resistance. Systematized information might be used in breeding programs, crop management, training and maintenance of germplasm banks bean.